MINIMIZING THE NUMBER OF PROCESSING UNITS IN DISTRIBUTED COMPUTATIONS - N. S. Kovalenko; V. N. Vengherov; V. M. Metelyskij (Informatika)
Polynomial algorithms for finding the minimum number of processing units in the problem of scheduling heterogeneous competing processes on parallel processors are developed. The algorithms ensure minimum completion time of all the processes and their completion by the specified deadline.